2022
DOI: 10.3389/fcell.2022.917575
|View full text |Cite
|
Sign up to set email alerts
|

Considering the Role of Extracellular Matrix Molecules, in Particular Reelin, in Granule Cell Dispersion Related to Temporal Lobe Epilepsy

Abstract: The extracellular matrix (ECM) of the nervous system can be considered as a dynamically adaptable compartment between neuronal cells, in particular neurons and glial cells, that participates in physiological functions of the nervous system. It is mainly composed of carbohydrates and proteins that are secreted by the different kinds of cell types found in the nervous system, in particular neurons and glial cells, but also other cell types, such as pericytes of capillaries, ependymocytes and meningeal cells. ECM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 249 publications
0
1
0
Order By: Relevance
“…Frontiers in Molecular Neuroscience 14 frontiersin.org Clasadonte et al 10.3389/fnmol.2023.1324922 evidence in the literature supports the role of Reelin in granule cell dispersion related to TLE (Leifeld et al, 2022). Reelin is a secreted glycoprotein present in the extracellular matrix that acts as a stop signal for neuronal migration during development (Tissir and Goffinet, 2003) but its function in adult hippocampus is not studied.…”
Section: Thioredoxin Peroxidase Activity Selenofmentioning
confidence: 99%
“…Frontiers in Molecular Neuroscience 14 frontiersin.org Clasadonte et al 10.3389/fnmol.2023.1324922 evidence in the literature supports the role of Reelin in granule cell dispersion related to TLE (Leifeld et al, 2022). Reelin is a secreted glycoprotein present in the extracellular matrix that acts as a stop signal for neuronal migration during development (Tissir and Goffinet, 2003) but its function in adult hippocampus is not studied.…”
Section: Thioredoxin Peroxidase Activity Selenofmentioning
confidence: 99%
“…Granule cells in epilepsy models are known to undergo significant change. These changes include mossy fiber sprouting, migration to ectopic locations, and formation of new, disorganized dendrites ( Hester and Danzer, 2014 ; Leifeld et al, 2022 ). These mossy fiber changes are related to dendritic spine morphological changes, as development of new widely spread dendrites and creation of new dendritic spines with increased density in areas proximal to mossy fiber sprouting are observed during migration of developing granule cells ( Puhahn-Schmeiser et al, 2022 ).…”
Section: Dendritic Spines and Epilepsymentioning
confidence: 99%
“…It controls neuronal migration and layer formation in the developing cerebral cortex, as evidenced by morphological studies on reeler mutant mice that lack reelin expression [36,37]. Reelin also modulates synaptic plasticity in the adult brain [38,39]. It has been shown that in the absence of reelin, experience-dependent plasticity in the visual cortex into adulthood was prolonged [40].…”
Section: Introductionmentioning
confidence: 99%